Effect of storage at 5°C on the bacterial flora and physical properties of Malaysian fishballs - Yu, S. Y.; Lee, C. C. (Asian Fisheries Society, 1995)
Fishballs from six local factories were stored at 5°C for 1, 2, 3, 4, 7 and 10 d. There were no changes in texture at 3 d of storage but bacterial spoilage rendered the fishballs unacceptable by the fourth day. Most of the bacteria were non-halophilic. The main genera isolated were Aerococcus, Acinetobacter, Pseudomonas, Staphylococcus, Corynebacterium, Micrococcus, Streptococcus and Enterobacteria.